The Development of Smart Apps Creator-based Interactive Media to Improve Narrative Text Writing Skills - Titin Amelia; Sri Sukasih (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
Writing skills are among the crucial abilities in education. This study pertained to the students' lack of narrative text-writing skills. The lack of  carefull selection of interactive media might impact the quality of learning process This investigation aims to measure the feasibility, practicality, and effectiveness of Smart Apps Creator-based interactive media to enhance the narrative text writing skills of grade-four students. Analysis, design, development, implementation, and evaluation comprising the ADDIE research model were employed. The outcomes of media validation feasibility revealed a 92% % percentage, and the material validation results revealed a proportion of 91%, so both were in the "Very Valid" category. Undoubtedly, the responses of 27 students and grade IV teachers were overwhelmingly positive, with the Smart Apps Creator usefulness-based interactive media scoring a perfect 100%. Regarding the effectiveness of the average N-Gain results, six small group students got the amount of 0,78, and 21 large group students got the amount of 0,71, both in the "High" category. Through this explanation, it is concluded that Smart Apps Creator's efficiency-based interactive media enhances the skills of writing narrative texts for grade IV students.